Edge Intelligence in Enhancing Last-Mile Delivery Logistics - Joao Reis (IEEE Access)
The last-mile delivery phase, the final stage where goods move from a distribution center to customers, is pivotal, but faces significant inefficiencies and high costs due to its complexity. Recent advancements in Edge AI or Edge Intelligence (EI) offer promising solutions to these challenges. This study explores how AI-driven technologies and real-time data processing, combined with EI, can enhance last-mile delivery operations. A thorough literature review was conducted to assess technological advancements by using PRISMA 2020, and a Delphi method was used to systematically and empirically assess the impact of EI solutions on operational efficiency and customer satisfaction. Although EI technologies offer substantial benefits, EU companies are hesitant to adopt these innovations due to high implementation costs. However, firms that have embraced these technologies report significant improvements, including better route optimization, reduced delivery times, and enhanced service reliability. These findings highlight the need for a culture of innovation and the recruitment of experts with advanced qualifications to drive technological advancement in last-mile logistics. The integration of EI represents a significant step towards more efficient, cost-effective, and customer-focused last-mile delivery solutions. Future research should refine use-cases of these technologies and explore their long-term impacts on logistics.